Analysis of Occupational Mental Health Status and Influencing Factors among Tertiary Industry Workers - Yuqin Wen; Yu Luo; Jie Xu (Journal of Artificial Intelligence and Information, 2026)
Objective: This study investigates and statistically analyzes the mental health issues of workers in the tertiary industry, examining the influencing factors to provide empirical evidence for the development of strategies aimed at promoting occupational mental health. Methods: A cross-sectional study was conducted. A total of 2,705 front-line workers from five industries—environmental sanitation, transportation, education, delivery/takeout and healthcare—were selected using cluster sampling. Participants’ physical and mental health status was assessed using the *National Survey Questionnaire on Occupational Health Literacy among Key Populations*. Statistical analyses were performed using the chi-square test and logistic regression models. Results: The findings revealed that mental health problems were prevalent among tertiary industry workers, with sleep disorders (90.1%) and depressive symptoms (74.0%) being particularly prominent. Depression risk in female workers was primarily associated with structural social inequalities. Age exhibited differential effects: occupational stress peaked in the 30~